Integration of food raw materials, food microbiology, and food additives: systematic research and comprehensive insights into sweet sorghum juice, Clostridium tyrobutyricum TGL-A236 and bio-butyric acid - Liu, Mei-Han; Zhou, Xiang; Zhang, Miao-Miao; Wang, Ya-Juan; Zhou, Bo; Ding, Nan; Wu, Qing-Feng; Lei, Cai-Rong; Dong, Zi-Yi; Ren, Jun-Le; Zhao, Jing-Ru; Jia, Cheng-Lin; et al. (Frontiers in Microbiology, 2024)
Introduction: Sweet sorghum juice is a typical production feedstock for natural, eco-friendly sweeteners and beverages. Clostridium tyrobutyricum is one of the widely used microorganisms in the food industry, and its principal product, bio-butyric acid is an important food additive. There are no published reports of Clostridium tyrobutyricum producing butyric acid using SSJ as the sole substrate without adding exogenous substances, which could reach a food-additive grade. This study focuses on tailoring a cost-effective, safe, and sustainable process and strategy for their production and application. Methods: This study modeled the enzymolysis of non-reducing sugars via the first/second-order kinetics and added food-grade diatomite to the hydrolysate. Qualitative and quantitative analysis were performed using high-performance liquid chromatography, gas chromatography-mass spectrometer, full-scale laser diffraction method, ultra-performance liquid chromatography-tandem mass spectrometry, the cell double-staining assay, transmission electron microscopy, and Oxford nanopore technology sequencing. Quantitative real-time polymerase chain reaction, pathway and process enrichment analysis, and homology modeling were conducted for mutant genes. Results: The treated sweet sorghum juice showed promising results, containing 70.60 g/L glucose and 63.09 g/L fructose, with a sucrose hydrolysis rate of 98.29% and a minimal sucrose loss rate of 0.87%. Furthermore, 99.62% of the colloidal particles and 82.13% of the starch particles were removed, and the concentrations of hazardous substances were effectively reduced. A food microorganism Clostridium tyrobutyricum TGL-A236 with deep utilization value was developed, which showed superior performance by converting 30.65% glucose and 37.22% fructose to 24.1364 g/L bio-butyric acid in a treated sweet sorghum juice (1:1 dilution) fermentation broth. This titer was 2.12 times higher than that of the original strain, with a butyric acid selectivity of 86.36%. Finally, the Genome atlas view, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and evolutionary genealogy of genes: Non-supervised Orthologous (eggNOG) functional annotations, three-dimensional structure and protein cavity prediction of five non-synonymous variant genes were obtained. Conclusion: This study not only includes a systematic process flow and in-depth elucidation of relevant mechanisms but also provides a new strategy for green processing of food raw materials, improving food microbial performance, and ensuring the safe production of food additives.